The Influence of Competence and Work Discipline on the Performance of Personnel at Kodim 1801/Manokwari - Donny, Agus Prihanto (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2026)
Kodim 1801/Manokwari is a military organization which has the main task of organizing combat and territorial training. However, in its implementation, Kodim 1801/Manokwari experienced problems where there were still individuals whose performance did not fully reach the expected performance standards. In overcoming these problems, it is important for Kodim 1801/Manokwari to improve the competency and work discipline of personnel. This research aims to determine the influence of competence and work discipline on the performance of Kodim 1801/Manokwari personnel. This research uses a descriptive method with a quantitative approach. The sampling technique in this research used purposive sampling with a sample size of 75 respondents using the Slovin formula. The results of the descriptive analysis show that the competency and work discipline of personnel are in the sufficient category, which indicates a need for further improvement. The results of data analysis show that competence and work discipline have a significant positive influence on the performance of Kodim 1801/Manokwari personnel. This research recommends strategic steps to improve personnel performance, including continued efforts in capacity building through relevant training, coaching, and field experience. Additionally, regular evaluation of performance and providing constructive feedback is necessary to help personnel improve and develop brand capabilities.